2016
DOI: 10.1371/journal.pone.0160399
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Safety and Liking Associated to the Colour Intervention of Bike Lanes: Contribution from the Behavioural Sciences to Urban Design and Wellbeing

Abstract: The perception of colour and its subjective effects are key issues to designing safe and enjoyable bike lanes. This paper addresses the relationship between the colours of bike lane interventions—in particular pavement painting and intersection design—and the subjective evaluation of liking, visual saliency, and perceived safety related to such an intervention. Utilising images of three real bike lane intersections modified by software to change their colour (five in total), this study recruited 538 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…How to deploy bike paths and bike lanes in order to create the optimal structure of bicycle infrastructures is becoming a trendy research topic. Indeed the number and the quality of bike facilities are positively related to the number of cyclists [ 4 , 5 ]. To this end, a fine understanding of cyclist behaviors is crucial to deploy bike facilities efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…How to deploy bike paths and bike lanes in order to create the optimal structure of bicycle infrastructures is becoming a trendy research topic. Indeed the number and the quality of bike facilities are positively related to the number of cyclists [ 4 , 5 ]. To this end, a fine understanding of cyclist behaviors is crucial to deploy bike facilities efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…The way motor vehicles and bicycles are separated is also an important factor, although physical separation usually makes the rider feel safer [15], and it is difficult to implement separation at intersections. Colored pavement is a better alternative [16], as is advancing the stop line by 3-5 m, which can also reduce the interference of bicycles by motor vehicles [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Chile, coloured cycle lanes have been created with both different colours and different patterns (Vera-Villarroel et al, 2016). A survey was designed with pictures of three different patterns (full paint, chessboard-pattern or stripes) with the colour manipulated to five different colours (white, yellow, blue, red, or green), resulting in 15 different combinations.…”
Section: Introductionmentioning
confidence: 99%
“…All pictures were then shown with the same three questions regarding perceived safety, salience, and liking. They found that colour explained more of the variance than pattern and that red was consistently given higher scores on the dependent variables (Vera-Villarroel et al, 2016). The three items used were all focussed on the colour (e.g., "the colour of this bike lane intersection seems appropriate for my safety") and not on evaluations of the cycle lanes as a whole and if people ignored other aspects of the cycle lane this could have inflated any colour-specific effects.…”
Section: Introductionmentioning
confidence: 99%